PENCARIAN JATI DIRI TOKOH UTAMA DALAM FILM “JALAN YANG JAUH, JANGAN LUPA PULANG”: ANALISIS HIERARKI KEBUTUHAN ABRAHAM MASLOW - Putri Silvia; Ayu Anggraeini Br. Simbolon; Sanada Manalu; Tomi Arianto (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze the hierarchy of needs in the main character of the film " A Long Way to Come Home ". In this study the author used a qualitative descriptive method. Data source The source of data is secondary data, namely the summary script of the film. This research uses Abraham Maslow's literary psychology regarding the hierarchy of needs. The research results in the study show that there are five needs that are achieved in the main character in the movie " A Long Way to Come Home ". The level shows the physiological needs of the main character Aurora when she eats, drinks, and shelter. The need for security is obtained by Aurora by her social environment which makes her feel that . The need for love is obtained from her friendship environment, which always helps and loves Aurora as their family too. Appreciation needs, obtained through how she can take care of herself, and do things that maintain her self-esteem. Self-actualization in the main character Aurora, seen how Aurora managed to meet her physiological, security, love, and appreciation needs.